2003
DOI: 10.1046/j.1365-2362.2003.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of endogenous pancreatic enzyme secretion by oral pancreatic enzyme treatment

Abstract: Exogenous applied pancreatic enzymes, dose- and time-dependently inhibited endogenous pancreatic secretion. The obtained results strongly support the existence of a protease mediated feedback mechanism in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…There is some evidence that at least in the short term, exogenous pancreatic enzyme supplements lead to inhibition of endogenous pancreatic secretion. 19 A genetic predisposition to intermittent decreased secretion leading to sludging in the pancreatic ducts of PS patients with CF has been postulated as one cause of pancreatitis. 3 One can speculate that chronic pharmacologic inhibition of pancreatic secretion by exogenous pancreatic enzyme supplements could be additive and potentially transform a PS patient to one who is PI.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that at least in the short term, exogenous pancreatic enzyme supplements lead to inhibition of endogenous pancreatic secretion. 19 A genetic predisposition to intermittent decreased secretion leading to sludging in the pancreatic ducts of PS patients with CF has been postulated as one cause of pancreatitis. 3 One can speculate that chronic pharmacologic inhibition of pancreatic secretion by exogenous pancreatic enzyme supplements could be additive and potentially transform a PS patient to one who is PI.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that dietary fibre interferes with the negative feedback regulation of pancreatic enzyme secretion leading to increased pancreatic exocrine function. Levels of pancreatic exocrine secretion have been evidenced to be regulated by intraluminal enzyme concentration through oral or duodenal addition of enzymes (Morisset, 2008;Walkowiak, Witmanowski, Strzykala, Bychowiec, Songin, Borski, et al, 2003). It was previously observed that participants fed a diet supplemented with 20g/day fibre for 4 weeks increased total postprandial pancreatic lipase output (Dukehart, Dutta, & Vaeth, 1989).…”
Section: Dietary Fibre and Pancreatic Exocrine Physiologymentioning
confidence: 99%
“…Alternatively, the increase in CCK and pancreatic fluid secretion into the intestine is inhibited by presence of trypsin in the intestine as well as other digestive enzymes ( 38 ). This feedback is accomplished via the CCK-releasing peptide in such that with the absence of peptides, CCK-releasing factor will be inactivated by trypsin and thus CCK secretion is decreased ( 28 ).…”
Section: Physiology and Regulation Of Pancreatic Secretionmentioning
confidence: 99%